Combined Orthopaedic and Infectious Disease Periprosthetic Joint Infection Clinic Enhances Arthroplasty Fellowship Training: A Survey From a Tertiary Center - Eric S. Dilbone, MD; Justin Leal, MD; Sean P. Ryan, MD; Thorsten M. Seyler, MD, PhD; Jessica L. Seidelman, MD, MPH; William A. Jiranek, MD (Arthroplasty Today, 2025)
Background: The rising incidence of periprosthetic joint infections (PJIs) is linked to increasing utilization of total joint arthroplasty and higher rates of obesity, diabetes, and immunosuppression. Despite preoperative risk factor modification and perioperative antibiotic interventions, PJIs remain difficult to prevent and diagnose. Treatment typically requires surgery and prolonged antibiotics. A combined orthopaedics and infectious disease (OID) clinic has emerged as an effective model for managing PJIs, but its utility for trainee education remains underexplored. Methods: In 2020, a combined OID clinic was established at the reporting institution, staffed by arthroplasty fellows and musculoskeletal infectious disease physicians. Fourteen past arthroplasty fellows who participated in the clinic from 2020 to 2024 were sent an anonymous survey consisting of 10 questions to evaluate how their experience influenced their development as clinicians and its relevance to their current practice. Results: All 14 eligible past arthroplasty fellows responded to the anonymous survey. Most respondents (71%) were in academic practice, with others in hospital employment (21%) or private practice (7%). PJI cases comprised 0%-40% of their clinical load. A total of 85% of fellows reported that the multidisciplinary clinic approach prepared them for managing PJIs, and 93% felt this experience would be beneficial for future fellows. Respondents agreed that a half day clinic once per month was sufficient. Conclusions: Arthroplasty fellows found the combined OID clinic valuable for managing PJI patients in their practice. Fellowship programs should consider incorporating such clinics to enhance training in PJI management. Level of evidence: Level IV, Therapeutic Study.